Nucleos(t)ide analogues potentially activate T lymphocytes through inducing interferon expression in hepatic cells and patients with chronic hepatitis B - Ai-Sheng Ho; Jungshan Chang; Shou-Dong Lee; Zong-Lin Sie; Hui-Fen Shih; Chun Yeh; Cheng-Liang Peng; Kapil Dev; Chun-Chia Cheng (Scientific Reports, 2024)
Abstract Chronic hepatitis B (CHB) leads to liver inflammation and dysfunction, resulting in liver fibrosis and cancer. Nucleos(t)ide analogues (NAs), inhibitors of hepatitis B virus (HBV), specifically suppress HBV replication. We proposed that immune modulation benefits seroconversion by HBsAg loss. However, activation of T lymphocytes also deteriorates hepatic inflammation. Therefore, we intended to investigate the T cell status and its relationship with hepatic functions in CHB patients treated with NAs. Serum markers, including liver function markers AST, ALT, and HBV-infected markers HBV DNA, HBsAg, HBeAg, and HBsAb were measured in the clinical routine. The T cell levels and markers, including CD69, CD107a, CXCR3, and PD-1 were investigated using flow cytometry. Meanwhile, IFNγ, IL-2, and CXCL10 as immune activation markers in the PBMCs were investigated using qPCR. To validate the effects of NAs on T cell status, qPCR and flow cytometry were used to investigate the gene expression in the HepG2 and PLC5 cells treated with NAs, and in the healthy PBMCs treated with the cell-cultured supernatant. We found that NAs significantly suppressed HBV DNA and reduced AST and ALT levels in the CHB patients. Meanwhile, AST and ALT were both positively correlated with activation marker CD107a in CD8+ T cells. In addition, we found that the CHB patients with seroconversion exhibited a higher CD4/CD8 ratio (p < 0.05) compared to non-seroconversion. We demonstrated that NAs potentially induced IFNs and PD-L1 expression in HepG2 and PLC5 cells. Moreover, the collected supernatant from NAs-treated HepG2 significantly activated PBMCs. This study revealed that the reduction of HBV by NAs may be the reason leading to less AST and ALT levels. We further demonstrated that NAs induced IFN expression in hepatic cells to potentially activate T lymphocytes, which was positively associated with AST and ALT levels in the CHB patients. The results may explain the phenomena in clinical that when the virus is reactivated by aborted use of NAs, it causes consequent T cells-mediated severe acute-on-chronic liver injury.